New clinical staging for pharyngeal surgery in obstructive sleep apnea patients, - Vidigal,Tatiana Aguiar (2014)
Introduction: The success of pharyngeal surgery in the treatment of obstructive sleep apnea syndrome depends on the appropriate selection of patients. Objective: To propose a new staging for indication of pharyngeal surgery in obstructive sleep apnea syndrome. Methods: A total of 54 patients undergoing extended tonsillectomy were retrospectively included, divided into six stages. Stage I: patients with palatine tonsils grade 3/4 and modified Mallampati index 1/2; stage II: palatine tonsils 3/4 and modified Mallampati index 3/4; stage III: palatine tonsils 1/2 and modified Mallampati index 1/2; stage IV: palatine tonsils 1/2 and modified Mallampati index 3/4; stage V: body mass index ≥40 kg/m2 with palatine tonsils 3/4 and modified Mallampati index 1, 2, 3, or 4. Stage VI: body mass index ≥40 with palatine tonsils 1/2 and modified Mallampati index 1, 2, 3, or 4. Results: The surgical success rates were 88.9%, 75.0%, 35.7%, 38.5%, and 100.0% in stages I–V. Conclusion: The presence of hypertrophic palatine tonsils was the anatomical factor in common in the most successful stages (I, II, and V), regardless of body mass index. Although the modified Mallampati index classes 3 and 4 reduced the success rate of surgery in patients with hypertrophic tonsils (stage II), the presence of modified Mallampati index classes 1 and 2 did not favor surgical success in patients with normal tonsils (stage III).